Gross ecosystem product accounting in Miyun County: the supply and use of ecosystem services - Shen, Yu-qian; Yi, Xiao; Chen, Meng; Ouyang, Zhi-yun (Frontiers in Ecology and Evolution, 2024)
 Compared the supply capacity and use status of ecosystem services in Miyun County.  Potential gross ecosystem product represents the extent and condition of ecosystem, while actual gross ecosystem product represents local population and economic conditions.  Potential gross ecosystem product is mainly affected by natural ecosystem area and vegetation coverage. Actual gross ecosystem product is mainly affected by GDP and population.  When the actual gross ecosystem product exceeded the local potential gross ecosystem product, it indicated that the utilization of the ecosystem by the local human society exceeded its capacity threshold, which would reduce the supply capacity of the ecosystem and thus affected the future ability of the ecosystem to 2 provide for human well-being.